53 Does the Community Geriatrician's Role in Advanced Care Planning Help Community Dwellers Achieve Their Preferred Place of Care?. (6th February 2020) - Honney, K; Judd, H; Mitchell, A; Nash, H; Ford, J; Schweigart, A; Griffiths, B; Sira, A
Abstract: Introduction: Advanced Care Planning (ACP) is well established for patients with terminal cancer diagnoses but is poorly utilised when caring for elderly patients with other terminal illnesses. We aimed to assess the effectiveness of ACP in our older, community dwellers following a period of increased awareness. Methods: A closed loop audit was undertaken, assessing deaths from a dementia care home within rural Norfolk, before and after implementation of an education and focus programme (cycle 1=Jan 2017-Jan 2018, cycle 2: Feb 2018-Jan-2019). Deceased patients were identified from care home records and data from electronic hospital and general practice records were analysed. Results were compared according to existing guidance outlined in the Palliative Gold Standards Framework (GSF) and Department of Health End of Life Care Strategy 2009. Compliance between cycles was compared using the chi-square test with p=.05 indicative of statistical significance. Results: 59 patients were included (median age=84, male=31). Results of the audit for each criterion are shown in table 1. More patients achieved their preferred place of care (PPOC) following the implementation of the education programme, with access to end of life medications significantly improving. Conclusions: Increasing awareness and understanding of ACP in the community has been shown to improve compliance with GSF standards, particularly access to end of life medications. Further efforts are still required to improve care and a third cycle is scheduled for January 2020, following further training.